Bloch‐based MRI system simulator considering realistic electromagnetic fields for calculation of signal, noise, and specific absorption rate. Issue 1 (4th September 2013) - Cao, Zhipeng; Oh, Sukhoon; Sica, Christopher T.; McGarrity, John M.; Horan, Timothy; Luo, Wei; Collins, Christopher M.
<x xml:space="preserve">Abstract</x> Purpose To describe and introduce new software capable of accurately simulating MR signal, noise, and specific absorption rate (SAR) given arbitrary sample, sequence, static magnetic field distribution, and radiofrequency magnetic and electric field distributions for each transmit and receive coil. Theory and Methods Using fundamental equations for nuclear precession and relaxation, signal reception, noise reception, and calculation of SAR, a versatile MR simulator was developed. The resulting simulator was tested with simulation of a variety of sequences demonstrating several common imaging contrast types and artifacts. The simulation of intravoxel dephasing and rephasing with both tracking of the first order derivatives of each magnetization vector and multiple magnetization vectors was examined to ensure adequate representation of the MR signal. A quantitative comparison of simulated and experimentally measured SNR was also performed. Results The simulator showed good agreement with our expectations, theory, and experiment. Conclusion With careful design, an MR simulator producing realistic signal, noise, and SAR for arbitrary sample, sequence, and fields has been created. It is hoped that this tool will be valuable in a wide variety of applications. Magn Reson Med 72:237–247, 2014. © 2013 Wiley Periodicals, Inc.